2020
DOI: 10.3389/fgene.2020.00311
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Coexpression Network Analysis of Features That Control Cancer Stem Cells Reveals Prognostic Biomarkers in Lung Adenocarcinoma

Abstract: Purpose: We aimed to identify new prognostic biomarkers of lung adenocarcinoma (LUAD) based on cancer stem cell theory.Materials and Methods: RNA-seq and microarray data were obtained with clinical information downloaded from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases. Weighted gene coexpression network analysis (WGCNA) was applied to identify significant module and hub genes. The hub genes were validated via microarray data from GEO, and a prognostic signature with prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 56 publications
(53 reference statements)
4
53
0
Order By: Relevance
“…In term of immunity, the overexpression of SRGs, which was positively related to cancer stemness, was associated with reduced immune infiltration. The findings were in accordance with previous studies (Limagne et al, 2016;Liu et al, 2018;Malta et al, 2018;Miranda et al, 2019;Liao et al, 2020). It has been reported that transcriptome-derived stromal and immune scores have implications for patient survival, metastasis and recurrence (Liu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In term of immunity, the overexpression of SRGs, which was positively related to cancer stemness, was associated with reduced immune infiltration. The findings were in accordance with previous studies (Limagne et al, 2016;Liu et al, 2018;Malta et al, 2018;Miranda et al, 2019;Liao et al, 2020). It has been reported that transcriptome-derived stromal and immune scores have implications for patient survival, metastasis and recurrence (Liu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This series of external veri cation fully demonstrated the feasibility and accuracy of our signature (Fig. 6) [23].…”
Section: Validation Of the Signature In Geomentioning
confidence: 55%
“…If not treated promptly and effectively, RA can seriously reduce the quality of life and even cause disability. There is no doubt that understanding diseases at the molecular level will help to improve their diagnosis and treatment [26,27].…”
Section: Discussionmentioning
confidence: 99%